Efektivitas Layanan Bimbingan Kelompok untuk Meningkatkan Motivasi Belajar dan Mengurangi Perilaku Membolos Siswa - Safitri, Nur’aini; Neviyarni, Neviyarni; Irianto, Agus (Konselor, 2014)
The low learning motivation and behavior of truant one of the problems in education that requires actions to sustainable reduction in the future. Group guidance services by leveraging dynamics group of students will obtain variety information that can help to overcome the various problems that life can be effective (KES) back. This research is a quantitative experiment design using form of quasi-experiment with the design of the non equivalent control group. The purpose of this study to increase the learning motivation and reduce behavior of truant students by implementing group guidance services. The subjects were students of grade IX from two schools, namely SMP Negeri 26 Padang (control group) and SMP Negeri 29 Padang (experimental group). Samples were taken by using purposive sampling with criteria that students who have low learning motivation and behaving truant more than three days in a month. The data collect using learning motivation scale with Likert model and student attendance recapitulation which then analyzed using the Wilcoxon Signed Ranks Test and Mann-Whitney 2 Independent Samples. The  study  revealed  that: (1) there was a significant differences between the learning motivation and behavior of truant students experimental group before and after group guidance services, where the average score of students motivation to increase and frequency behavior of truant s students decreased after treatment, (2) there was a significant differences between the learning motivation and behavior of truant students control group before and after information services, where the average score of students motivation to increase and frequency behavior of truant students decreased after treatment, (3) there  was  not  a significant difference between the learning motivation and behavior of ditching the control group students with student the experimental group after a given treatment, and (4) the application group guidance service is more effective to improve learning motivation and reduce the frequency behavior of truant students compared with information services, where the average score of motivation to learn the experimental group is higher and the frequency behavior of truant the experimental group was lower than with the control group after treatment.